Food Policy Modelling Responses to Current Issues - Mattas, Konstadinos; Baourakis, George; Zopounidis, Constantin; Staboulis, Christos (Cham : Springer International Publishing : Imprint: Springer, 2022)
In the present economic, political, societal and environmental landscape, which is dominated by the COVID-19 pandemic, the emergence of challenges and issues that demand immediate and urgent responses is more intense than ever. Policymakers, international organizations, governmental and non-governmental institutions around the globe are seeking effective and sustainable policies, as they try to tackle far-reaching issues that affect all aspects of the economy and agriculture, including the food sector. In this context, this book presents new modelling approaches and their application to complex problems in the agro-food chain in order to address today's pressing food policy issues. The respective chapters showcase national and regional studies on sustainable communities, rural environments and ecosystems. Taken together, they offer a valuable reference guide for scholars and practitioners alike.".
1. The Effect of Financial and Non-financial Factors on the Productivity and Profitability of the Goat Industry: A Modelling Approach to Structural Equations -- 2. Initiating Transition to Agro-ecological Farming Systems in Market-Oriented Arable Farming with Soil Conservation Practices: A Case Study in Hungary -- 3. Competitiveness, Sustainability Performances and Policy Options in the Sheep Meat Sector of Mediterranean Countries -- 4. Countries' Image and Agricultural Trade Volume -- 5. Designing a Traceability Framework for Sustainable Agri-Food Supply Chains -- 6. Digitalization in the EU Agricultural Sector: Seeking a European Policy Response -- 7. Why Go on Vacation to Crete? Assessing the Role of Local Cuisine -- 8. Consumer Preferences for Local Food Products Marketed by Women's Cooperatives.
Keywords: Management; Sustainability; Agriculture-Economic aspects; Management; Sustainability; Agricultural Economics